Prenatal developmental safety of functional polyurethanes for cardiovascular implants. Issue 3 (7th May 2015) - Gu, Yongjiang; Sun, Fan; Xie, Xingyi; Wu, Xiangyang; Zhang, Ze; Guidoin, Robert; Fu, Qiang; Zhong, Yinping; Zhao, Changsheng
Abstract: Historically, polyurethanes have been regarded as promising materials for cardiovascular implants such as vascular grafts and heart valves. Their biocompatibility has been thoroughly investigated. However, their developmental toxicity is seldom reported. We recently developed two polycarbonate urethanes with polyethylene glycol side chains capped with epoxy or amino groups that can further react with specific biomolecules. Both materials in microfibrillar morphology were subjected to saline extraction at 70°C to prompt material hydrolysis. Proton nuclear magnetic resonance, Fourier transform infrared spectroscopy, and gel permeation chromatography all confirmed the degradation of the polyurethanes. The saline extracts containing the degradation products were administered to Sprague‐Dawley female rats on day 7 to 16 of gestation via tail vein injection at a dose of 5 mL/kg/day. No maternal toxicity was observed. No external, skeletal, and visceral malformations in fetuses were found associated with the test materials, implying their safety to both adult rats and the offspring. Further investigations for applications in vascular grafts are under way. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 606–614, 2016.